Attitudes Towards Juvenile Offenders in Serbia: An Exploratory Study - Karić, Tijana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
In this study, we explored the attitudes of the general public towards juvenile offenders. Participants (N = 1264), aged 18–87 (M = 34), responded to a 17-item scale created based on public comments to news about juvenile offending on news portals and social media. Socio- demographic characteristics were also collected. The analysis revealed three interpretable factors: Fatalistic view, Accountability, and Family factors. The highest scores were obtained on the Accountability, and the lowest on the Fatalistic view factor. Older participants, participants who are married, those who are parents, men, lower educated, and participants from rural areas hold harsher attitudes towards juvenile offenders. Those who have not had contact with juvenile offenders tend to attribute more responsibility to family factors. Of those who have been in contact with juvenile offenders, those who have higher scores on the Fatalistic view and Accountability describe the contact as more negative.